Design of Weakly Cationic Alco-Cryogels Consisting of Poly (Alkylmethacrylates)-Based Sulfonated Terpolymer Network with Tunable Multiresponsive Assembly - BEŞLİ, NUR SENA ÖKTEN; Orakdogen, Nermin (Elsevier Science Ltd., 2021)
Cryogels with ion-, and solvent-responsiveness have been designed by cryogelation of 2-(diethylamino)ethyl methacrylate (DEAEMA) as weakly cationic monomer, hydroxyethyl methacrylate as neutral comonomer and 2- acrylamido-2-methyl-1 -propanesulfonic acid as anionic termonomer in ethanol-water mixture (50:50 v/v), which had been proved to offer a good miscibility of monomers. Influence of composition of terpolymer and polymerization temperature on the properties of terpolymer cryogels (Cgels) and hydrogels (Hgels) were evaluated by swelling kinetics, and response against rapid ionic strength change. Degree of swelling was extremely sensitive to salt concentration, cation/counterion type as well as the solvent type; acetone and monohydric alcohols with various hydrophobic alkyl groups; methanol, ethanol, and 2-propanol. Swelling of terpolymer networks in the form of Cgel and Hgel decreased with increase in the size of ions present in swelling medium and followed the order of swelling behavior CF- > Br- > I-. Terpolymer alcogels exhibited salting-out behavior in the presence of Cl- and Br(- )ions, while "salting-in" behavior was observed in KI solutions of high concentrations. Sensitivity sequence of terpolymer alcogels to mono- and di-valent cations with a common anion (SO42-) on swelling was Na+ > k(+) > Mg2+ > Zn2+. Variation of elastic moduli with swelling in salt solutions was investigated and for terpolymer hydrogels, possible contribution of ionic crosslinks to effective crosslinking density nu(e) was discussed. Increasing Na2SO4 concentration up to 0.1 M induced a 2-fold increase in the elastic modulus of terpolymer alcogels. With attention to the polarity of solvent, terpolymer gels exhibited an irregular swelling profile with a change in composition of solvent, showing the so called cosolvency phenomena. After two successive cycles of swelling and shrinking promoted by the change of ionic strength of KCl solution, the terpolymer gels were stable and dynamic swelling process was reversible. Swelling data agree well with second-order kinetic model and with increasing amount of DEAEMA in terpolymer feed, diffusion mechanism changed from non-Fickian type to Fickian diffusion. In ionic environments, the salt-sensitivity and excellent water absorption/retention capability give this intelligentized terpolymer gels wide potential applications.
Keywords: Compression; Multiresponsive Networks; Alkylmethacrylates; Cationic Alcogels